Psychiatric disorders in patients with benign and malignant sinonasal tumors: a prospective cross-sectional study - Zhan, Guang-Ye; Wang, Hui-Fang; Wang, Dong-Fang; Wen, Yi-Hui; Zhong, Hua; Wen, Wei-Ping; Li, Jian; Peng, Liang (Frontiers in Psychology, 2024)
Objective: To assess the prevalence of depression, anxiety, insomnia, and somatic symptom disorder (SSD) in patients with benign and malignant sinonasal tumors.: Pretreatment patients with sinonasal tumors were prospectively recruited on the rhinology ward of a tertiary hospital from July 2021 to March 2022. The electronic questionnaire which contains the rhinological symptom scale, 22-item Sinonasal Outcome Test (SNOT-22) scale, Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), Insomnia Severity Index (ISI), and Patient Health Questionnaire-15 (PHQ-15) was filled out by patients at admission. The associations between symptom /SNOT-22 scores and scores of psychometric tests were assessed by the Pearson correlation coefficient (r) and simple linear regression. Receiver operating characteristic (ROC) analysis was used to evaluate the performance of the SNOT-22 score in predicting psychiatric disorders.Results: Thirteen patients with benign sinonasal tumors and fifteen patients with malignant sinonasal tumors were recruited. The benign and malignant groups did not differ significantly regarding symptomatology and mental well-being. Of the total patients, 9 were at risk of depression (PHQ-9 > 4), 10 were at risk of anxiety (GAD-7 > 4), 11 were at risk of insomnia (ISI > 7), and 11 were at risk of SSD (PHQ-15 > 4). The overall symptom, facial pain/pressure, postnasal drip, and SNOT-22 scores were positively associated with scores of psychometric tests. Patients with a high SNOT-22 score (> 18) are likely to be affected by comorbid psychiatric disorders.When interpreting the results of this study, it should be noted that screening tools, not diagnostic tools, were used to identify psychiatric risk.Depression, anxiety, insomnia, and SSD are prevalent in patients with sinonasal tumors. Otolaryngologists should have a low threshold to ask the patient about psychiatric symptoms, especially for patients with a SNOT-22 score > 18.